G547(P) Oh my… a very unusual coincidence! the case of a boy who developed haemolysis following a trip to the swimming pool. (May 2019) - Bell, A; Hughes, J; Williams, C; Knox, S
Abstract : A 2 year old boy presented to his GP with a 2 day history of pyrexia, cough and mild diarrhoea. His family were concerned that he had developed striking pallor and mild jaundice after going swimming the previous day. He was referred to his local DGH for further assessment. At presentation he was noted to be tachycardic, mildly jaundiced and very pale. Mild splenomegaly was noted on abdominal ultrasound. Haemoglobin was 30 g/L with a reticulocyte count 15.6%. Blood film showed nucleated red blood cells and infrequent spherocytes. Blood cross match revealed cold agglutinins most frequently associated with mycoplasma pneumoniae infection. A blood transfusion was required for treatment of anaemia. Mycoplasma pneumoniae is a major cause of community acquired pneumonia in children. Infection with the organism is a rare cause of secondary cold agglutinin disease. A type of haemolytic anaemia in which, in cold environments, IgM antibodies attach to red blood cells and cause haemolysis. In this case we believe the trigger for the haemolysis was this boy's trip to the swimming pool the day before his admission to hospital. Treatment involves eradication of the underlying cause of the agglutinin production (in this case with azithromycin) and supportive management of anaemia. Following eradication of the underlying cause prognosis is excellent and in most patients there is resolution of the condition within six months. In the meantime, avoidance of low temperatures is advised.